2015
DOI: 10.1016/j.bjid.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of efficacy and safety of doripenem for treating bacterial infections

Abstract: From this meta-analysis, we can conclude that doripenem is as valuable and well-tolerated than empirical antimicrobial agents for complicated intra-abdominal infections, complicated urinary tract infection, acute biliary tract infection and nosocomial pneumonia treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
1
11
1
4
Order By: Relevance
“…Additionally, the clinical success rate was 89.4% and ranged from 70.3% to 100.0%. Our findings are in line with the findings of a review [16] of several clinical trials conducted by Lo et al and a recent meta-analysis [17], both of which reported that doripenem was not inferior to the comparators, such as meropenem, imipenem, piperacillin/tazobactam, or levofloxacin, in its efficacy and safety profile in patients with a wide range of serious hospital-acquired infections. Thus, these results suggest that doripenem may serve as an effective treatment option in the armamentarium of antibiotics available to treat HCAIs.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the clinical success rate was 89.4% and ranged from 70.3% to 100.0%. Our findings are in line with the findings of a review [16] of several clinical trials conducted by Lo et al and a recent meta-analysis [17], both of which reported that doripenem was not inferior to the comparators, such as meropenem, imipenem, piperacillin/tazobactam, or levofloxacin, in its efficacy and safety profile in patients with a wide range of serious hospital-acquired infections. Thus, these results suggest that doripenem may serve as an effective treatment option in the armamentarium of antibiotics available to treat HCAIs.…”
Section: Discussionsupporting
confidence: 92%
“…В целом дорипенем оказался не хуже препаратов сравне-ния (меропенем, имипенем, пиперациллин/тазобактам, левофлоксацин) по показателям эффективности и безо-пасности при лечении пожилых пациентов с наличием Эти данные совпадают с результатами метаанализа 6 клинических исследований, опубликованного в 2015 г. и посвященного эффективности и безопасности приме-нения дорипенема при различных осложненных вне-больничных и нозокомиальных инфекциях [4]. Мета-анализ показал, что дорипенем так же эффективен, как препараты сравнения, у пациентов с осложненными абдоминальными инфекциями, осложненными уро-инфекциями и пиелонефритом, острыми инфекциями билиарного тракта и нозокомиальной пневмонией, включая НПивл.…”
Section: клинические исследования дорипенема при тяжелых нозокомиальнunclassified
“…Позже в рамках метаанализа всех рандомизирован-ных клинических исследований дорипенема была отдель-но проанализирована группа из 3 исследований, специ-ально посвященных применению дорипенема у пациен-тов с нозокомиальной пневмонией и НПивл, целью кото-рого была оценка эффективности и безопасности именно для этой группы пациентов [4,8,10,11]. Препаратами сравнения в этих исследованиях были те, которые на момент исследования имелись в протоколах лечения нозокомиальной пневмонии или НПивл (пиперациллин/ тазобактам и имипенем/циластатин).…”
Section: клинические исследования дорипенема при нозокомиальной пневмunclassified
“…Дорипенем демонстрировал аналогичную препаратам сравнения частоту нежелательных явлений и показатели смертности от всех причин (для частоты неже-лательных явлений ОШ = 1,10, 95% ДИ = 0,90-1,35, p = 0,33; для смертности от всех причин ОШ = 1,08, 95% ДИ = 0,77-1,51, p = 0,67). Дорипенем был не менее эффекти-вен и не менее безопасен по сравнению с другими пре-паратами при лечении НП и НП-ИВЛ [29].…”
Section: клиническая эффективность дорипенема при вентиляторассоциирunclassified